Buying Behavioural Model of Debit Card Consumers - A New Challenges for Indian Bankers - Nalini Prava Tripathy (Sinergi: Kajian Bisnis dan Manajemen, 2006)
There has been an exponential growth in the debit cards issuance and usage among the people. Today the debit card segment is highly competitive with almost all the banks offering debit cards in association with international or master card. Every bank is try-ing to gain a market share with aggressive promotional activities and additional value-added services. Keeping in view, the present study investigates the factors that are essential in influ-encing the decision-making styles of mid-age family of eastern India This study gives an in-sight to lure customers towards themKeywords: Behavioral model, debit card, mid age family.